Case of Inherited Partial AZFa Deletion without Impact on Male Fertility. (31st October 2019) - Alksere, Baiba; Berzina, Dace; Dudorova, Alesja; Conka, Una; Andersone, Santa; Pimane, Evija; Krasucka, Sandra; Blumberga, Arita; Dzalbs, Aigars; Grinfelde, Ieva; Vedmedovska, Natalija; Fodina, Violeta; et al.
Abstract : Male factor infertility accounts for 40–50% of all infertility cases. Deletions of one or more AZF region parts in chromosome Y are one of the most common genetic causes of male infertility. Usually full or partial AZF deletions, including genes involved in spermatogenesis, are associated with spermatogenic failure. Here we report a case of a Caucasian man with partial AZFa region deletion from a couple with secondary infertility. Partial AZFa deletion, involving part of USP9Y gene appears to be benign, as we proved transmission from father to son. According to our results, it is recommended to revise guidelines on markers selected for testing of AZFa region deletion, to be more selective against DDX3Y gene and exclude probably benign microdeletions involving only USP9Y gene.